In Vivo Administration of Mycobacterial Cord Factor (Trehalose 6,6′-Dimycolate) Can Induce Lung and Liver Granulomas and Thymic Atrophy in Rabbits - Hamasaki, Naoko (American Society for Microbiology, 2000)
Trehalose 6,6′-dimycolate (TDM) is a cell surface molecule of Mycobacterium tuberculosis. TDM induced a loss of body weight and prominent granulomas in the liver and lungs by the intravenous injection of TDM into rabbits. TDM also induced atrophy of the thymus and spleen due to apoptosis. By contrast, sulfolipid (2,3,6,6′-tetraacyl trehalose 2′-sulfate) induced neither toxicity, nor granuloma formation, nor atrophy of the thymus and spleen. In rabbits the histopathological changes were more dramatic than in mice. The rabbit model may be more sensitive and may provide more information on the beneficial or pathological effects of TDM.